Comparative analysis of the main business process modeling methods: a bibliometric study - Tulio Cremonini Entringer; Ailton da Silva Ferreira; Denise Cristina de Oliveira Nascimento (Gestão & Produção, 2021)
Abstract The offer of business process modeling methodologies is quite extensive, making it difficult for scholars in the BPM area to choose properly. In this context, this paper has the objective to present the main modeling methodologies, with applications, examples and comparisons. A systematic bibliographic survey and the comparative analysis of these notations used in the implementation of BPM projects have been carried out. According to the bibliometric analysis, the modeling notations of the business process most portrayed in the works surveyed are: BPMN, UML, EPC and IDEF. From the construction of a consistent overview that allows the comparative analysis of the methodologies, in order to select the one that suits better its specificities it can be verified that, although they share the same objective, each notation has its specific characteristics. This study has the main purpose of providing a basis for the adequate indication of the application of studies in the field, especially those destined for papers, dissertations and theses.